2022
DOI: 10.1111/jfd.13688
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic analysis of Edwardsiella isolates from Taiwan indicates wide variation with a particular reference to Edwardsiella tarda and Edwardsiella anguillarum

Abstract: Edwardsiella spp. is a gram‐negative, facultatively anaerobic, intracellular bacteria threatening the aquaculture industry worldwide. Noticeably, E. tarda is now genotypically classified into three distinct groups (E. tarda, E. piscicida and E. anguillarum), but morphologically, it is unclear due to varying degrees of virulence in different fish hosts. Hence, to reclassify E. tarda, we investigated differences in genotypes, phenotypes and pathogenicity. We collected Edwardsiella isolates from five different co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Our study is the first to utilize Nanopore technology to identify aquaculture pathogens at the species level of E. anguillarum and E. piscicida from diseased cultured fish in Taiwan. Moreover, with the application of genome sequencing, this study confirmed the species taxonomy as E. anguillarum or E. piscicida based on the gyr B gene sequence in a previous study (Rahmawaty et al, 2022). The unique findings with regard to the genomes of E. anguillarum and E. piscicida will facilitate the investigation of epidemiology, intraspecies diagnostic methods, vaccine development, and drug treatment for both species.…”
Section: Introductionsupporting
confidence: 86%
See 4 more Smart Citations
“…Our study is the first to utilize Nanopore technology to identify aquaculture pathogens at the species level of E. anguillarum and E. piscicida from diseased cultured fish in Taiwan. Moreover, with the application of genome sequencing, this study confirmed the species taxonomy as E. anguillarum or E. piscicida based on the gyr B gene sequence in a previous study (Rahmawaty et al, 2022). The unique findings with regard to the genomes of E. anguillarum and E. piscicida will facilitate the investigation of epidemiology, intraspecies diagnostic methods, vaccine development, and drug treatment for both species.…”
Section: Introductionsupporting
confidence: 86%
“…In this study, we evaluated two E. anguillarum and E. piscicida strains, which were recently isolated from milkfish ( Chanos chanos ) and Japanese eel ( Anguilla japonica ) in Taiwan. The virulent properties of these two bacteria in milkfish indicated variation in mortality as demonstrated in a recent study (Rahmawaty et al, 2022). Therefore, we sequenced the genome to understand the species identification and compare their genomic characteristics by using Oxford nanopore MinIon technology, which identifies DNA bases by measuring the changes in electrical conductivity generated as DNA strands pass through a biological pore (Lu et al, 2016).…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations